2022
DOI: 10.3390/bios12060430
|View full text |Cite
|
Sign up to set email alerts
|

How Does Lower Limb Respond to Unexpected Balance Perturbations? New Insights from Synchronized Human Kinetics, Kinematics, Muscle Electromyography (EMG) and Mechanomyography (MMG) Data

Abstract: Making rapid and proper compensatory postural adjustments is vital to prevent falls and fall-related injuries. This study aimed to investigate how, especially how rapidly, the multiple lower-limb muscles and joints would respond to the unexpected standing balance perturbations. Unexpected waist-pull perturbations with small, medium and large magnitudes were delivered to twelve healthy young adults from the anterior, posterior, medial and lateral directions. Electromyographical (EMG) and mechanomyographical (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…e ., where the test participant knew when the moment of unbalance would take place). It would seem that increased Vcop and TCI_dV values should result in a different TCI number as a reaction of the nervous system aimed to coordinate the activity of individual muscles [ 26 29 ]. Additional analysis of TCI_dS and TCI_dT revealed that the observed increase in both velocities was primarily due to the extension of the path of momentary leaps of COP (TCI_dS) while maintaining constant times between leaps (TCI_dT) and consequently the same number of TCI.…”
Section: Discussionmentioning
confidence: 99%
“…e ., where the test participant knew when the moment of unbalance would take place). It would seem that increased Vcop and TCI_dV values should result in a different TCI number as a reaction of the nervous system aimed to coordinate the activity of individual muscles [ 26 29 ]. Additional analysis of TCI_dS and TCI_dT revealed that the observed increase in both velocities was primarily due to the extension of the path of momentary leaps of COP (TCI_dS) while maintaining constant times between leaps (TCI_dT) and consequently the same number of TCI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have found an increase in time to peak activation of various ankle muscles (with the exception of PL, which has not been studied) in the elderly compared with young adults. A longer time to peak activation of a muscle correlates with a lower rate of force generation and a reduction in sufficient postural responses [ 50 , 52 ]. Possible reasons for the difference in results are the muscles tested, because different muscles may be affected differently, and the type, direction, or speed of the perturbation performed in each study, which may also affect muscle response [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…By comparing healthy walking, functional electrical stimulation (FES)-assisted walking, and non-FES walking, they have observed some asymmetric activation patterns in the investigated cortical areas for stroke survivors. Regarding the motor output pathway, recent studies have investigated the speed of multiple major lower-limb muscles' activation in maintaining reactive standing balance by analyzing the timing and rising rate of electromyographic (EMG) signals, revealing that ankle muscles have the faster response ( 2 , 3 ). In addition to EMG, with the advancing of wearable technologies, some techniques, such as the ultrasound imaging of muscles, have been available to detect the muscle morphological changes in dynamic situations and assess balance performance ( 4 , 5 ).…”
Section: Probing the Balance-control Mechanismsmentioning
confidence: 99%